Price transmission for agricultural commodities in Uganda: An empirical vector autoregressive analysis - Kaspersen, Line Lassen; Helene Ystanes Føyn, T. (International Food Policy Research Institute, 2010)
This paper investigates price transmission for agricultural commodities between world markets and the Ugandan market in an attempt to determine the impact of world market prices on the Ugandan market. Based on the realization that price formation is not a static concept, a dynamic vector autoregressive (VAR) model is presented. The prices of Robusta coffee and sorghum are examined, as both of these crops are important for the domestic economy of Uganda - Robusta as a cash crop, mainly traded internationally, and sorghum for consumption at household level. The analysis focuses on the spatial price relations, i.e. the price variations between geographically separated markets in Uganda and the world markets. Our analysis indicates that food markets in Uganda, based on our study of sorghum price transmission, are not integrated into world markets, and that oil prices are a very determining factor for price transmission within the country. However, the case is a bit different for the cash crop, Robusta coffee. In the period in the 1990's with high coffee prices on the world market, prices in Uganda were strongly connected to world prices, and did not depend on the oil price. This indicates that if high demand appears in world markets, such effects could transmit to local markets. Thus, price transmission from world markets has only been evident in the case of booming prices of an exported commodity, but otherwise agricultural commodity markets are poorly linked. The empirical analysis thus indicates that rising food prices (of little-traded crops) on world markets will not have a direct effect on food prices in Uganda.